Patočka y Henry. A-subjetividad y Fenomenología material: dos modalidades de realismo fenomenológico - Di Pierro, Eduardo González (Bollettino Filosofico, 2018)
As is well-known, the Czech philosopher Jan Patočka is one of the most important and sharp continuers of Husserl phenomenology: in an inevitable critical relationship he aims at overcoming Husserl’s perspective, always accurately taking into account the Master’s thought. Patočka has always focalized his attention on the so to say objective aspect of Husserl’s phenomenology. However, he presents an interesting explanation of the subjective one through a reformulation of the phenomenological project in the moment of its foundation in Logical Investigations. It has caused several misunderstandings, thus Patočka’s phenomenology has been defined an “asubjective phenomenology”, leading to the inclusion of Patočka among the so-called “realist phenomenology” of the Göttingen Circle. This is totally incorrect, as we can see in several passages, in which Patočka interprets and comments Husserl’s phenomenology. The article only examines some considerations in Plato and Europe and in Patočka’s Introduction to Husserl’s Phenomenology. Patočka’s criticism to Husserl allows at the same time to clarify the transcendental considerations expressed in the first paragraphs of Ideas I, that converge in the core of the conclusions of the point 55 of the work. Here we can see that Husserl’s supposed “transcendental idealism” is not a return to a form of German classical idealism, but it is rather a peculiar form of “realism” different from the way it has interpreted by the first followers of Husserl.